2017
DOI: 10.1371/journal.pone.0172942
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk factors associated with smear positivity of pulmonary tuberculosis in Kazakhstan

Abstract: BackgroundSputum smear-positive tuberculosis (TB) patients have a high risk of transmission and are of great epidemiological and infection control significance. Little is known about the smear-positive populations in high TB burden regions, such as Kazakhstan. The objective of this study is to characterize the smear-positive population in Kazakhstan and identify associated modifiable risk factors.MethodsData on incident TB cases’ (identified between April 2012 and March 2014) socio-demographic, risk behavior, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
2
17
1
2
Order By: Relevance
“…Interestingly, while different studies were able to describe association between alcohol abuse and TB [17][18][19], we are the first to describe the relationship between alcohol abuse and Xpert performances.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, while different studies were able to describe association between alcohol abuse and TB [17][18][19], we are the first to describe the relationship between alcohol abuse and Xpert performances.…”
Section: Discussionmentioning
confidence: 88%
“…In the final multilevel model adjusted per CF and overcrowding at the second level, no sociodemographic characteristics lost association. Young adults (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) were 93% more likely (PRa 1.93; 95% CI: 1.49-2.51) to be diagnosed with srTB than older adults (>55), and male participants had 10 times more chance to be diagnosed with srTB (PRa 10.06; 95% CI: 3.86-26.25). Those who born in the capital were 28% more likely to have srTB (PRa 1.28; 95% CI: 1.09-1.50) compared to other provinces.…”
Section: Resultsmentioning
confidence: 99%
“… 45 The authors found that alcohol consumption (≥ 2 drinks per day) were associated with an increased risk of tuberculosis when accompanied by smoking (hazard ratio = 1.51; 95% CI: 1.11-2.05), which is another risk factor for the development of active tuberculosis. 46 …”
Section: Risk Factors For Tuberculosismentioning
confidence: 99%
“…Individuals with AUD are considered more infectious because AUD has been associated with the finding of cavitary disease on chest X-rays and therefore with smear positivity. 46 , 47 In addition, AUD has been associated with higher rates of treatment default (OR = 1.99; 95% CI: 1.04-3.81) and relapse (OR = 3.9; 95% CI: 2.5-6.1). 48 , 49 There are several reasons for that, including precarious living conditions and the increased risk of hepatotoxicity due to tuberculosis treatment in this group of patients.…”
Section: Risk Factors For Tuberculosismentioning
confidence: 99%